Preferred Formation of Minority Concomitant Polymorphs in 2D Self‐Assembly under Lateral Nanoconfinement. (21st August 2019) - Seibel, Johannes; Amabilino, David B.; De Feyter, Steven
Abstract: Control over polymorph formation in the crystallization of organic molecules remains a huge scientific challenge. Now, preferential formation is presented of one polymorph, formed by chiral molecules, in controlled two‐dimensional (2D) nanoconfinement conditions at a liquid–solid interface. So‐called nanocorrals to control concomitant polymorph formation were created in situ via a nanoshaving protocol at the interface between 1‐phenyloctane and covalently modified highly‐oriented pyrolytic graphite (HOPG). The preferentially formed polymorphs, which were less stable in the large‐scale monolayers, could be selected simply by varying the orientation of the square nanocorrals with respect to the HOPG lattice. Abstract : Eingezäunt : In situ hergestellte Nanogehege können selektiv die Bildung von einem der zwei Polymorphe induzieren, die sonst gleichzeitig an der Grenzfläche von 1‐Phenyloctan und hoch orientiertem pyrolytischem Graphit erscheinen.